2013
DOI: 10.1136/bcr-2013-009231
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal leiomyosarcoma masquerading as laryngeal carcinoma

Abstract: Laryngeal leiomyosarcoma is an exceedingly rare malignant tumour, with fewer than 50 reported cases in scientific literature. Diagnosis is based on immunohistochemistry, supplemented with ultrastructural studies, if required. It is aggressive and associated with variable survival outcomes. A 63-year-old man presented with hoarseness for 7 months and breathlessness for 3 months. Imaging showed a well-defined 3 cm glottic mass. Total laryngectomy was performed. The histopathological examination showed features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…LLMS is uncommon; we identified 62 cases in the English‐language literature (Table 1). 1,3–55 Tangjaturonrasme found that the number of LLMS cases was increasing; four cases were reported from 1961 to 1970, compared to 21 cases from 2000 to 2010. This may be a result of advances in diagnostic techniques, including immunohistochemical techniques and electron microscopy 46 .…”
Section: Discussion/literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…LLMS is uncommon; we identified 62 cases in the English‐language literature (Table 1). 1,3–55 Tangjaturonrasme found that the number of LLMS cases was increasing; four cases were reported from 1961 to 1970, compared to 21 cases from 2000 to 2010. This may be a result of advances in diagnostic techniques, including immunohistochemical techniques and electron microscopy 46 .…”
Section: Discussion/literature Reviewmentioning
confidence: 99%
“…Most patients had overlapping presentations: 8 of 61 (13.1%) had hoarseness and dyspnea, and 14 of 61 (23.0%) had hoarseness/stridor/dyspnea/dysphagia. Ten of sixty‐one patients (16.4%) had emergency tracheostomy for serious dyspnea 14,17,28,33,35,39,43,46,47,53 . The laryngoscopic manifestations of LLMS are diverse.…”
Section: Discussion/literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations